Chest compression quality, exercise intensity, and energy expenditure during cardiopulmonary resuscitation using compression-to-ventilation ratios of 15:1 or 30:2 or chest compression only: a randomized, crossover manikin study - Kwak, Se-Jung (Clin Exp Emerg Med, 2016)
OBJECTIVE: Our aim was to compare the compression quality, exercise intensity, and energy expenditure in 5-minute single-rescuer cardiopulmonary resuscitation (CPR) using 15:1 or 30:2 compression-to-ventilation (C:V) ratios or chest compression only (CCO). METHODS: This was a randomized, crossover manikin study. Medical students were randomized to perform either type of CPR and do the others with intervals of at least 1 day. We measured compression quality, ratings of perceived exertion (RPE) score, heart rate, maximal oxygen uptake, and energy expenditure during CPR. RESULTS: Forty-seven students were recruited. Mean compression rates did not differ between the 3 groups. However, the mean percentage of adequate compressions in the CCO group was significantly lower than that of the 15:1 or 30:2 group (31.2±30.3% vs. 55.1±37.5% vs. 54.0±36.9%, respectively; P<0.001) and the difference occurred within the first minute. The RPE score in each minute and heart rate change in the CCO group was significantly higher than those of the C:V ratio groups. There was no significant difference in maximal oxygen uptake between the 3 groups. Energy expenditure in the CCO group was relatively lower than that of the 2 C:V ratio groups. CONCLUSION: CPR using a 15:1 C:V ratio may provide a compression quality and exercise intensity comparable to those obtained using a 30:2 C:V ratio. An earlier decrease in compression quality and increase in RPE and heart rate could be produced by CCO CPR compared with 15:1 or 30:2 C:V ratios with relatively lower oxygen uptake and energy expenditure.